LECTORA INSPIRE INTERACTIVE LEARNING MEDIA AS A LEARNING INNOVATION - Kurniawan, Andri (Pedagogi, 2024)
In the technology sector used of information and communication technology is a tremendous output. Support of technolgy information is hoped to become an innovation in learning with many involving information technology components inside. This paper discusses the interactive learning media that involve education technology using lectora inspire application. I think in lectora inspire is designed specifically for the beginner with purpose user friendly to use to make learning media to easy, can make the material test or evaluation and is to be interested student to be happy in his studied. The development of interactive learning media with lectora inspire is conducted with how to provide training to the teachers in the elementary school. The methods are done with phases, includes gathering information, planning tools, implementing, presenting and reflecting. The object of this training is Regional technical implementing unit, state elementary school education unit SDN TANGERANG 14 and Regional technical implementing unit, state elementary school education unit SDN SUKASARI 5.